Depresión y consumo de alcohol en adolescentes de padres migrantes de la comunidad de Oñacapac, período 2022 - Morocho Saca, Janeth Isabel (2022)
The depression is a mental illness that can appear at any age; the adolescence is a vulnerable stage where you can deal with it, due to the different type of changes the person can suffer during his or her develop it will face to different circumstances that can put at risk his or her mental health. Furthermore, the use of alcohol is one of the behaviours can be related with. Also, a factor that can increase the vulnerability to develop both problematics, is the absence of parents who play the protective and modulator role. For that reason, the present study it had as an objective to stablish the relation between depression and alcohol consumption at the adolescence stage with parents who have emigrate in the community of Oñacapac, using the quantitative type approach, non-experimental, descriptive-correlational design and cross sectional, in which participated 82 teenagers which parents migrate between ages of 15 and 19, selected through non- probability sampling for convenience in a total population of 103 teens. As a data collection instrument, it was used a Sociodemographic File, the Beck Depression Inventory II (BDI II) and the Alcohol Use Disorders Identification Test (AUDIT). For the statistical descriptive and inferential analysis, it was used the SPSS 22. The results show that exist a direct but meaningful low relation between depression and alcohol disorder in the sample study (p=0,021<0.05; rs=0,255); minimal and mild depression in a 76.9%, together with lowrisk and risky consumption in a 81.7%, are the most prevalent levels. Considering these results, a prevent program was proposed with the main objective to avoid exacerbation of the same with more serious levels